Travessia de canais por dutos: um guia e uma ferramenta para a estimativa da profundidade de erosão - Pelizzaro, Jairo Antonio (2009)
Pipeline crossings of mobile-bed rivers must be the subject of thorough analysis and careful design considerations, since they are highly susceptible to the instability instability of the bed and the banks during floods. The present work comprises a basic guide and a tool to estimate the erosion of channel bed at pipeline crossings. The work lists the empirical methods for sediment transport calculations and their equations. The usefulness of HEC-6, a computer model which allows the prediction of bed changes, is also considered for the calculating erosion at pipeline crossings.. Data is collected on the field for 10 pipeline crossings, in the state of Minas Gerais, Brazil, near the town of Barbacena. The data required for topographical and hydraulic characterization of each pipeline crossing is listed, and the analysis tool herein developed, in the form of spreadsheets for each empirical method, is presented. The results thus obtained are then compared with those given by HEC-6. Finally, a comparison is made between the estimates obtained herein and the design values for a pipeline that will connect Rio de Janeiro to Belo Horizonte, showing good agreement.